The effects of school-based hygiene intervention programme: Systematic review and meta-analysis. - Sophia Rasheeqa Ismail; Ranina Radzi; Puteri Sofia Nadira Megat Kamaruddin; Ezarul Faradianna Lokman; Han Yin Lim; Nusaibah Abdul Rahim; Hui Yin Yow; Daarshini Arumugam; Alex Ngu; Annie Ching Yi Low; Eng Hwa Wong; Sapna Patil; et al. (PLoS ONE)
Children are susceptible to infections due to frequent participation in school group activities and their often-suboptimal hygiene practices. Frequent infections in children affect school attendance, academic performances, and general health. The effectiveness of school-based hygiene-related intervention programmes need to be informed by updated high-quality synthesised evidence. In this systematic review, we searched PubMed and Cochrane CENTRAL for randomised and non-randomised interventional studies that evaluated school-based hygiene-related interventions. We assessed risk-of-bias (Cochrane risk-of-bias 2 tool), performed random-effect meta-analysis (RevMan 5.4) and rated certainty-of-evidence (GRADE). Thirty-nine trials (41 reports), published from 2011 to 2024 from 22 countries were included. Twenty-three studies contributed data for meta-analysis. All school-based interventions were compared with standard curriculum and demonstrated very low to low certainty-of-evidence due to study methodological limitations and imprecision. Hand-body hygiene interventions may improve knowledge, attitudes and practices (SMD 2.30, 95%CI 1.17 to 3.44, 6 studies, 7301 participants), increase handwashing practices (RR 1.75, 95%CI 1.41 to 2.17, 5 studies, 5479 participants), and reduce infection-related absenteeism (RR 0.74, 95%CI 0.66 to 0.83, 5 studies, 1017852 observations). Genital hygiene interventions may improve attitude (SMD 6.53, 95%CI 2.40 to 10.66, 2 studies, 2644 participants) and practices (RR 2.44, 95%CI 1.28 to 4.68, 1 study, 1201 participants). However, intervention effects on oral hygiene appeared mixed, with worsening of the oral hygiene score (SMD 3.12, 95%CI 1.87 to 4.37, 2 studies, 652 participants) but improved dental hygiene (SMD -0.33, 95%CI -0.53 to -0.13, 3 studies, 4824 participants) and dental caries scores (SMD -0.34, 95%CI -0.52 to -0.16, 4 studies, 2352 participants). Limited evidence suggests that interventions targeting hand-body and genital hygiene practices may improve knowledge, practices, and infection-related absenteeism. However, the effects on oral hygiene intervention appeared mixed. Future research should strengthen randomisation and intervention documentation, and evaluate hygiene-related behaviour, academic performances and health outcomes.